2015
DOI: 10.1016/j.matdes.2014.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Characterising mode I/mode II fatigue delamination growth in unidirectional fibre reinforced polymer laminates

Abstract: In this paper, fatigue life estimation for delamination growth of laminated fibre reinforced polymer (FRP) composite structures in mode I and mode II based on fracture mechanics is presented. The proposed method was applied to delamination of glass/epoxy laminated composite. Both the threshold energy release rate ( ) and the delamination propagation based on Paris' law were studied. The double cantilever beam (DCB) specimen for mode I and 3 points End-Notched Flexure (3ENF) specimen for mode II were used for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…Delamination is a serious detriment to the stiffness and compressive load carrying capability of a FRP composite laminate [3,4] and this area has been investigated for new advanced nanomaterial to enhance the fracture toughness of FRP materials [5]. Manjunatha et al [6] studied the stress-controlled constant amplitude tensile fatigue tests at stress ratio R=0.1 on rubber modified GFRP composites.…”
Section: Introductionmentioning
confidence: 99%
“…Delamination is a serious detriment to the stiffness and compressive load carrying capability of a FRP composite laminate [3,4] and this area has been investigated for new advanced nanomaterial to enhance the fracture toughness of FRP materials [5]. Manjunatha et al [6] studied the stress-controlled constant amplitude tensile fatigue tests at stress ratio R=0.1 on rubber modified GFRP composites.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted results are non-conservative and also there is difference compared to experimental values. The delamination studies under static and fatigue loads have been shown to exhibit some significant scatter in test results [3,8,11,12]. The constant amplitude data shown in Fig.…”
Section: Interpolation Techniquementioning
confidence: 99%
“…Hojo et al [9,10] studied the effect of Z-direction stitching on the fatigue behavior of CFRP under mode I delamination and showed that up to 5 times higher fatigue threshold could be obtained by stitching. The mode I delamination growth under fatigue loading was investigated by several others [3,11,12] to characterize the growth behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Lucchini et al [15] studied the delamination mechanism of metal/polymer electrical interconnects with S-shaped planar meanders. Al-Khudairi et al [16] characterized the mode I and mode II delamination fatigue delamination growth in laminated fibre reinforced polymer (FRP) composite structures.…”
Section: Introductionmentioning
confidence: 99%